Pengaruh Flat Slab Terhadap Keruntuhan Progresif Pada Struktur Gedung Tidak Beraturan - Roni Suhendra; Zulfikar Djauhari; Ridwan Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Technological developments in the field of construction are currently more advanced, the structure of the building not only an regular but also irregular. Terraced building structure in the shape of irregular very influential towards the collapse of the building. The collapse of the building can be the collapse of the natural and the artificial collapse. It is a natural collapse collapse caused by load capacity by building or building exceeds the ability of the structure personally. Potentialities of the failure of the structure due to the collapse, can lead to progressive collapse. This research aimed to analyze the effect of flat slab to the collapse beharfour of irregular building structures, and determine the type of collapse that occurred at irregular building structures. This research was conducted by analyzing the elements of the structure destroyed in advance the result of addition of maximum load. The analysis done by eliminating one or more of the critical column based on General Service Administration (GSA) code. Examination of structural strength using finite element based software, valuebased Demand Capacity Ratio (DCR). Irregular building structures have a progressive collapse when the value of the DCR is more than 1 that. The results of the analysis indicated progressive collapse did not occur on the structure of the building, due to irregular use of the building elements that form the structure of a flat slab. The collapse happened on only some elements of the structure of the building, both elements of the structure of the beams as well as elements of the structure column. Since its collapse did not occur on the structure of the building, so the building collapse type could not be seen. Keywords: Progressive collapse, irregular structure, flat slab, GSA, DCR, finite element program.